Controlling Dispersion during Single-Cell Polyacrylamide-Gel Electrophoresis in Open Microfluidic Devices - Pan, Qiong (Anal Chem, 2018)
New tools for measuring protein expression in individual cells complement single-cell genomics and transcriptomics. To characterize a population of individual mammalian cells, hundreds to thousands of microwells are arrayed on a polyacrylamide-gel-coated glass microscope slide. In this “open” fluidic device format, we explore the feasibility of mitigating diffusional losses during lysis and polyacrylamide-gel electrophoresis (PAGE) through spatial control of the pore-size of the gel layer. To reduce in-plane diffusion-driven dilution of each single-cell lysate during in-microwell chemical lysis, we photo-pattern and characterize microwells with small-pore-size sidewalls ringing the microwell except at the injection region. To reduce out-of-plane-diffusion-driven-dilution-caused signal loss during both lysis and single-cell PAGE, we scrutinize a selectively permeable agarose lid layer. To reduce injection dispersion, we photopattern and study a stacking-gel feature at the head of each <1 mm separation axis. Lastly, we explore a semienclosed device design that reduces the cross-sectional area of the chip, thus reducing Joule-heating-induced dispersion during single-cell PAGE. As a result, we observed a 3-fold increase in separation resolution during a 30 s separation and a >2-fold enhancement of the signal-to-noise ratio. We present well-integrated strategies for enhancing overall single-cell-PAGE performance.